Formal rules and institutional increments in Brazil - Jorge, Mario (Organizational crime, 2023)
Brazil’s anticorruption scenario has gone through major shifts in the last two decades. The changes we describe are part of the formal and institutional accountability networks. Major investigations, such as Mensalão and Car Wash, have opened up various discussion fronts, especially concerning the relationship between the economic and political sectors in Brazil. The means of control, investigation, and prosecution, in the form of new legislation and institutional organization, have been well developed in some areas, while others are still lacking, by international standards. Improved inter-institutional coordination and closer proximity among the agents that make up each of the entities in this system have also been pointed out as some of the positive factors for greater effectiveness. In the corporate landscape, compliance has an increasing rate of adoption, also due to stricter legislation. Some setbacks, however, have recently been identified in the legal and institutional anticorruption frameworks, especially regarding institutional independence.